2018
DOI: 10.1007/s11205-018-1957-5
|View full text |Cite
|
Sign up to set email alerts
|

From One Recession to Another: Longitudinal Impacts on the Quality of Life of Vulnerable Groups

Abstract: At the beginning of the 2000s, Switzerland went through two global recessions: the Dotcom crisis and the Great Recession. Even though Switzerland experienced milder effects compared to its European neighbours, the Swiss unemployment rate increased considerably compared to its status quo. This paper explores the resilience of vulnerable groups to these economic downturns using both objective (income poverty and material deprivation) and subjective (wellbeing and satisfaction with the financial situation) indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
(49 reference statements)
2
8
0
1
Order By: Relevance
“…In line with previous research on the economic effects of severe social and economic crises (e.g. Simona-Moussa and Ravazzini 2019 ) the authors found larger families (with three or more children) and single parents to be the hardest hit. The study thus confirms again that vulnerable families, i.e.…”
supporting
confidence: 87%
“…In line with previous research on the economic effects of severe social and economic crises (e.g. Simona-Moussa and Ravazzini 2019 ) the authors found larger families (with three or more children) and single parents to be the hardest hit. The study thus confirms again that vulnerable families, i.e.…”
supporting
confidence: 87%
“…Consistent with these mechanisms, research has found direct associations between unemployment and several financial outcomes, including financial satisfaction (Bonke and Browning 2009 ; Brown and Gray 2016 ; Simona-Moussa and Ravazzini 2019 ), difficulties managing financially (French 2018 ), and financial hardships (Scutella and Wooden 2004 ). Only two studies have investigated the effects of adverse labour market outcomes using comprehensive, summative measures of financial wellbeing.…”
Section: Introductionmentioning
confidence: 89%
“…Socialinis pažeidžiamumas yra viena iš svarbių pažeidžiamumo tyrimų atšakų, orientuotas į pažeidžiamą subjektą, t. y. asmenį ar populiaciją, ir apibrėžiamas kaip asmenų politinis, institucinis ar ekonominis pajėgumas tam tikroje erdvėje ir tam tikru laiku (Wisner, Blaikie, Cannon & Davis, 2004;Contemporary Sociology, 2018;Simona-Moussa & Ravazzini, 2019;Simona-Moussa, 2020;Prokazina, Alekseenok & Kaira, 2020). Ranci, Migliavacca (2010: 219) socialinį pažeidžiamumą apibrėžė kaip "gyvenimo situaciją, apibūdinamą atskirties ir įtraukties veiksnių daugiamate kombinacija".…”
Section: Socialiai Pažeidžiamos Gyventojų Grupės: Teorinis Požiūris Ir Vertinimų Apžvalgaunclassified